Gradle for Android : learn the new build system for Android development - Kousen, Ken; Safari eBooks ([Place of publication not identified] : O'Reilly, 2015)
"Whether you're new to Gradle or an experienced Android developer, Java consultant Ken Kousen will help you get better acquainted with the Gradle automated build system. With 'enough Groovy to get by,' you'll learn Groovy's relationship to Java and how it defines both static and dynamic variables. You'll also build and run a simple Android app, test it, and modify it to add capabilities. The video includes: Gradle basics: use a Gradle build for a Java project, define custom tasks and insert them into the Gradle directed acyclic graph, and add plugins using a buildscript; build types: create debug-and-release Android application packages (APK), and learn how to sign and prepare a release APK; run tests: test non-user interface components, specifically data access layers; use a third-party UI testing library: test UI components, and run tests on all connected devices simultaneously; define multiple flavors: create different versions of the same application, change images and other resources, and generate multiple APKs. In addition to learning how to build multi-module projects, you'll also add an Android library project to a top-level project, and use it to access a web service and update the UI."--Resource description page.
Title from title screen (viewed September 11, 2015).
Publication date from resource description page.
Presenter, Ken Kousen.
Keywords: Gradle (Computer file); Android (Electronic resource); Mobile apps -- Development; Mobile apps -- Testing; Electronic books